The influence of students’ interpersonal nature on adjustment to loss and grief on Kenyan orphaned Secondary school students - Owaa, Judith Anyango; Aloka, Peter J. O.; Raburu, Pamela A. (Mediterranean Center of Social and Educational Research, 2014)
The purpose of the study was to determine the influence of students’ interpersonal nature on adjustment to Loss and Grief on orphaned Kenyan secondary school students.The study was informed by Erikson’s Psychosocial Theory of Human Development. Mixed method research approach was used and with it, concurrent triangulation design was adopted. The target population consisted of 47 schools, 20 focus group discussion students, 10 personal interviews and 1,245 Form 3 orphaned students from public secondary schools in Kisumu Central Sub-County of Kenya. A sample size of 453 students from 15 secondary schools were sampled for the study using stratified random sampling technique. Reliability of the instruments was ascertained through a pilot study of 9% of the population that did not participate in the final study. Internal consistency was also used to determine the reliability of questionnaires and coefficient values of r=0.0771 was reported for the questionnaire. Face validity of the instruments was ascertained by pilot testing the questionnaires and also by seeking expert judgment by university lecturers. Data was collected by use of questionnaires, in-depth interviews and focus group discussions. Quantitative data was analyzed using both descriptive and inferential statistics. Qualitative data was analyzed using thematic framework. Trustworthiness of qualitative data was ensured by analyzing the framework as fronted by Lincoln & Guba (1985). The study findings revealed that there were significant differences on adjustment to loss and grief on the basis of interpersonal nature. Schools should assign teachers adoptive parenting roles for the orphaned students in school.
DOI: 10.5901/mjss.2015.v6n4s1p333
Keywords: Perceptions; Guidance; Counselling; Kenyan; Secondary school; Career decision making